A new integration strategy - Carlos Massad (CEPAL Review, 1989)
The Great Depression of the 1930s and the Second World War engendered an inward-directed growth process in Latin America, the continuance of which was later spurred by the important interests that grew up in connection with the region’s industrial production. The exhaustion of the import substitution process at the national level triggered a new intellectual effort to seek appropriate development strategies; thence arose the interest in economic integration which acquired great impetus from 1960 onwards. Integration enjoyed considerable success in terms of the expansion of trade among the countries participating in the various schemes, and mechanisms were soon added which helped to save foreign exchange in the financing of regional trade payments.